Psychological contract breach and employees’ demographic factors as predictors of workplace deviant behaviours in the Nigerian Banking Industry - Adekanmbi, Foluso Philip; Ukpere, Wilfred I (International Journal of Psychosocial Rehabilitation, 2018)
To some scholars, workplace deviant behaviours are seen as employees’ intentional actions, which differ from vital organisational values, and are menacing to an organisation’s wellbeing, that of her members, or both the organisation and her members. Additionally, this viewpoint regarding workplace deviant behaviours has similarly been adopted in the Nigerian banking industry. However, despite the rising focus on research regarding workplace deviant behaviours, and the creation of interventions to reduce it, a few interrelated problems remain ignored and are yet to be suitably examined. Therefore, the aim of this research is to examine psychological contract breach and employees’ demographic factors as predictors of workplace deviant behaviours in the Nigerian banking industry. This research adopted a quantitative research approach, as well as used one non-probability sampling method (purposive sampling) and two probability sampling, namely, stratified and simple random sampling. The findings of this paper indicated that psychological contract breach and some employees’ demographic factors significantly jointly predict workplace deviant behaviours in the Nigerian banking industry, However, it was found that psychological contract breach does not significantly, independently predict workplace deviant behaviours in the Nigerian banking industry. The findings further indicated that employees’ demographic factors (such as age, level of education, and work experience) significantly predict workplace deviant behaviours in the Nigerian banking industry. Notably, employees’ level of education and work experience negatively predict workplace deviant behaviours, while their age positively predicts it. Furthermore, the current investigation noticed that older employees (who are, 50 years old and above) are more prone to engaging in workplace deviant behaviours than younger employees (between, 20-34 years old, and 35-49 years old) in the Nigerian banking industry. The findings also suggested that employees who passed ICAN/CIBN/ACCA qualifications were significantly less disposed to engaging in workplace deviant behaviours compared to their colleagues who had MSC/MBA and HND/BSC qualifications. Additionally, the findings noted that employees who had 11 years of more of work experience were less likely to participate in workplace deviant behaviours, as opposed to their contemporaries who have about 1-5 years and 6-10 years of work experience in the Nigerian banking industry. Furthermore, this paper has established that employees’ perception of psychological contract breach did not make them engage in workplace deviant behaviours, and that employees’ demographic factors (such as age, level of education, and work experience) significantly predicted workplace deviant behaviours in the Nigerian banking industry.